Transformation of Information Technology Based on Human Computer Interaction Concept - Made Sudarma (Institute of Advanced Engineering and Science, 2013)
Transformation technology brings importance consequence to the management system improvement and expansion. In this case exploiting of Information Technology (IT) is hardly required to manage because of it affect to efficiency and effectiveness of the system. The purpose of this paper is to design Integrated Academic Management Information System (IAMIS) with concept of Human Computer Interaction (HCI). The method which be applied is qualitative method by using inductive analysis approach by ignoring initial hypothesis of the research, but to find patterns, forms and themes to expose data systematically. The final result is HCI applied in IAMIS system has been applied, so that found usability and functional system, effective and efficient of AIMIS system are fully be able to carry out well. Furthermore, the analysis results show using IAMIS system affected the staff productivity increasing by 12%, it also means affected in improvement of information services to the academic community. The writer recommended to design system on the concepts of HCI and accommodated is able to online (web-based) system.DOI: http://dx.doi.org/10.11591/ij-ict.v2i3.4115